2014
DOI: 10.3892/ol.2014.1795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AG490 and S3I-201 on regulation of the JAK/STAT3 signaling pathway in relation to angiogenesis in TRAIL-resistant prostate cancer cells in vitro

Abstract: The aim of the present study was to analyze the molecular mechanisms involved in blocking the signaling pathway and the effects of this on the progression of prostate cancer (CaP) cells in vitro. LNCaP human CaP cell line was stimulated with interleukin-6 (IL-6) in the presence/absence of Janus kinase (JAK) 2 (AG490), signal transducer and activator of transcription 3 [(STAT3) S3I-201] inhibitors and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Cytotoxic activity, the activation of phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…7E,F). This indicates that STAT3 may self-regulate, consistent with previous observations(54). Thus, in addition to NFκB, activation of STAT3 is critical for inducing DLL4 in PB DCs.…”
Section: Resultssupporting
confidence: 92%
“…7E,F). This indicates that STAT3 may self-regulate, consistent with previous observations(54). Thus, in addition to NFκB, activation of STAT3 is critical for inducing DLL4 in PB DCs.…”
Section: Resultssupporting
confidence: 92%
“…In addition, it has been reported that constitutive STAT3 activation contributed to oncogenesis by modulating angiogenesis,30 and our results showed that EP can down-regulate the STAT3 activity. Taken together, it is highly possible that EP may also attenuate tumor angiogenesis, which needs more experimental evidence.…”
Section: Discussionsupporting
confidence: 77%
“…Phosphorylated STAT3 dimerizes and translocates into the nucleus to bind to specific DNA response elements to induce the transcription of downstream genes, such as BCL-xL, MCL1 and c-Myc (32). Targeting STAT3 signaling results in suppression of the proliferation of various cancer cells in vitro and tumorigenicity in vivo (33,34). Therefore, the identification and development of novel drugs targeting deregulated STAT3 activation effectively remains an important scientific and clinical challenge (35,36).…”
Section: Discussionmentioning
confidence: 99%